Employee Recruitment and Selection Process in Building a Good Corporate (Case Study at Perumda Air Drinking Tirta Giri Nata Cirebon City) - Mia Audina Liawati; Virly Lika Syahlia; Ade Solahudin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the recruitment and selection process of employees in order to realize Good Corporate Governance at Perumda Air Minum Tirta Giri Nata, Cirebon City. Good corporate governance is essential for long-term organizational performance, and can be achieved through open and responsible employee selection. The purpose of this study is to examine the stages of employee recruitment and selection, as well as the extent to which the process complies with Good Corporate principles such as transparency, involvement, accountability, effectiveness, and law enforcement. This research uses descriptive qualitative method and case study methodology. Data were collected through interviews, observations, and documentation studies of the employee recruitment and selection process at Perumda Air Minum Tirta Giri Nata in Cirebon City. The study findings show that the company uses an open recruitment approach and strict selection, involving a third party to ensure neutrality. Furthermore, Good Corporate concepts have been implemented through accountability procedures, information transparency, fair staffing, and employee participation in decision-making. The findings of this study suggest that efficient recruitment and selection procedures help create strong corporate governance. This research is planned to be a resource for other companies that want to establish recruitment and selection procedures that comply with Good Corporate standards.